1996
DOI: 10.5636/jgg.48.233
|View full text |Cite
|
Sign up to set email alerts
|

A High Density Sampling K-Ar Dating of the Kinpu-San Plutonic Body and the Initiation of the Philippine Sea Plate Subduction.

Abstract: A detailed K-Ar and 40Ar-39Ar geochronological study was conducted on the Kinpu-san body, which is a part of the Kufu plutonic complex. We collected a sample from every 3 km x 3 km area in the body. The chronological study based on this high density sampling clearly illustrates that the body systematically becomes younger from north to south. The oldest age in the body could be considered to restrict the initiation time of the Philippine Sea plate subduction. Thus, we conclude that the subduction started 16 Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Experimental data can be found elsewhere (Saito and Kato 1996). The sampling locations (together with the K-Ar ages obtained) are shown in Fig.…”
Section: A K-ar Age Study On the Ashigawa Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data can be found elsewhere (Saito and Kato 1996). The sampling locations (together with the K-Ar ages obtained) are shown in Fig.…”
Section: A K-ar Age Study On the Ashigawa Bodymentioning
confidence: 99%
“…Shibata et al (1984) collected a sample from the Shosenkyo area and obtained a K-Ar date of 13.0 Ma. Saito and Kato (1996) dated 1 5 samples from the Kinpusan body and obtained K-Ar ages ranging from 11 to 16 Ma. The dates by previous workers fall in this range.…”
Section: Kinpusan and Kaikomagatake Bodiesmentioning
confidence: 99%
“…The KGC developed contact meta- morphic aureoles up to the amphibolite facies (Kato, 1968;Shimazu et al, 1976;Shimizu, 1986) and in some places anatectic migmatites were formed at the intrusive contact (Saito, in preparation). Geochronological studies on the KGC employing the K Ar dating method give ages ranging from 9 to 16 Ma (Shibata et al, 1984;Saito and Kato, 1996;Saito et al, 1997). K Ar ages of the Ashigawa intrusion and the southern part of the Tokuwa intrusion are 11.6 12.9 Ma (hornblende) and 11.9 12.5 Ma (biotite) .…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Various degrees of chrolitization may be responsible for these low contents. Several previous studies (Kulp and Engels, 1963;Saito and Kato, 1996) have suggested that chrolitization of 50% or more does not significantly affect the K-Ar age. It may be possible to argue that, when biotite weathers, alteration of the mineral occurred layer by layer and lost its Ar and K simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…In the South Fossa Magna, several plutons have formed since Miocene, when the Philippine Sea Plate started to subduct. Recent radiometric age investigations (Saito et al, 1991;Saito, 1993;Saito and Kato, 1996) have demonstrated that the Kinpusan pluton (the northwestern part of the Kofu plutonic complex) formed about 16 Ma and subsequently cooled ti1111-12 Ma, that the Tokuwa and Ashigawa body, which consist of the eastern and southern part of the Kofu plutonic complex, formed and cooled between 12 and 9 Ma, and the Tanzawa pluton formed at 6.7 Ma and subsequently cooled. In this same interval, several exotic terranes collided with central Japan to construct the South Fossa Magna.…”
Section: Previouslymentioning
confidence: 99%